The athletic trainer's guide to differential diagnosis a visual learning approach - Winterstein, Andrew P., 1962-; Clark, Sharon V., 1965- (SLACK Incorporated, 2015)
The Athletic Trainer's Guide to Differential Diagnosis; A Visual Learning Approach is designed to create a framework that allows the reader to think differently about differential diagnoses, access existing knowledge in anatomy and clinical evaluation, and assess information for the purpose of making higher-order clinical decisions.